Strategi Gerakan Gemar Membaca Dalam Meningkatkan Keterampilan Literasi Membaca Peserta Didik Kelas IV - Arini, Ni Ketut; Tresnawati, Ni Kadek; Swari, Ni Kadek Sukma; Astuti, Ni Ketut Desi Puja; Yuli, Ni Kadek; Werang, Basillius Redan (DAS Institute, 2024)
This study aims to discuss the implementation of reading enthusiasm strategies in an effort to improve the reading literacy skills of fourth grade students of SD Negeri 3 Pangkungparuk. This research was conducted with descriptive research using a qualitative research approach to obtain an overview of the implementation of reading literacy. Data collection in the study was carried out using the interview method so as to obtain data on how teachers carry out reading literacy activities in the classroom. Observations at SD Negeri 3 Pangkungparuk showed varied strategies in improving reading literacy, such as the reading movement which involves reading activities in the library and reading corners. This strategy aims to foster students' interest in reading so that it becomes a positive habit. Reading interest has a very important role for a learner, if learners do not have great interest and attention to what they are learning then it is difficult for these learners to be diligent and obtain good results in their learning. The results show that the strategies implemented are effective in increasing interest and reading literacy skills, with the support of an adequate library and reading corner. The role of teachers and a supportive learning environment are very important in fostering students' interest in reading and literacy skills